Equitable Research Partnerships A Global Code of Conduct to Counter Ethics Dumping - Schroeder, Doris; Chatfield, Kate; Singh, Michelle; Chennells, Roger; Herissone-Kelly, Peter (SpringerBriefs in Research and Innovation Governance,, 2019)
This open access book offers insights into the development of the ground-breaking Global Code of Conduct for Research in Resource-Poor Settings (GCC) and the San Code of Research Ethics. Using a new, intuitive moral framework predicated on fairness, respect, care and honesty, both codes target ethics dumping - the export of unethical research practices from a high-income setting to a lower- or middle-income setting. The book is a rich resource of information and argument for any research stakeholder who opposes double standards in research. It will be indispensable for applicants to European Union framework programmes, as the GCC is now a mandatory reference document for EU funding. .